Creación de una granja avícola en la Parroquia Caracol - MUÑOZ SANCHEZ, ARIEL ARMANDO (2020)
The present project of the mini chicken poultry farm is a strategic plan for the supply of chicken, this project will carry out its constitution in 2020 in the Caracol parish, a sector where the supply of chicken is insufficient for the population This project focuses on the sector to enter the market as its first mini-poultry farm, the POLLON mini-poultry farm will have an approximate of 5 employees who will take care of all the necessary steps for proper operation. This project has the feasibility of a greater amount of income due to the fact that the product that we offer is one of the most consumed nationwide after pork, on the other hand, the association with the stores, dining rooms and grills of the sector They will benefit to make a greater amount of sales of our product, to publicize our product we will focus on door-to-door advertising with the businesses in the sector, to carry out this project we will need an initial investment of $ 11,161.50 and thanks to this investment our earnings will be for each additional $ 5, 15 dollar invested and we must bear in mind that this will allow us to recover our investment in approximately 1 year 9 months and 9 days. Keep in mind that the personnel who will be in charge of the maintenance and management of the mini poultry farm will be chosen by selection, who must have the basic knowledge associated with raising broilers and maintaining the farm. This requirement will be exclusively for the shed, the person in charge of maintaining the farm's infrastructure, must have the necessary knowledge of mechanical electricity and welding, among other skills necessary to carry out the various services position; the general manager is the person who must know all the handling of the accounts and the purchase and sale of the company soon and the administrator is the person in charge of keeping a record of all activities of the company and in the legal field of its operation.